2016
DOI: 10.1371/journal.pone.0155906
|View full text |Cite|
|
Sign up to set email alerts
|

Mortality, Rehospitalisation and Violent Crime in Forensic Psychiatric Patients Discharged from Hospital: Rates and Risk Factors

Abstract: ObjectivesTo determine rates and risk factors for adverse outcomes in patients discharged from forensic psychiatric services.MethodWe conducted a historical cohort study of all 6,520 psychiatric patients discharged from forensic psychiatric hospitals between 1973 and 2009 in Sweden. We calculated hazard ratios for mortality, rehospitalisation, and violent crime using Cox regression to investigate the effect of different psychiatric diagnoses and two comorbidities (personality or substance use disorder) on outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
36
2
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 64 publications
4
36
2
5
Order By: Relevance
“…Previous studies on treatment outcome have suggested that the population of former forensic psychiatric inpatients remains at high risk for several adverse outcomes but seems to be at lower risk for reoffending in comparison with offenders without a mental disorder. In a longitudinal study of 6,520 patients (89.2% male) discharged from secure forensic psychiatric inpatient treatment in Sweden, Fazel, Wolf, Fimi nska, and Larsson (2016) found a high premature mortality rate of 29.9%…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on treatment outcome have suggested that the population of former forensic psychiatric inpatients remains at high risk for several adverse outcomes but seems to be at lower risk for reoffending in comparison with offenders without a mental disorder. In a longitudinal study of 6,520 patients (89.2% male) discharged from secure forensic psychiatric inpatient treatment in Sweden, Fazel, Wolf, Fimi nska, and Larsson (2016) found a high premature mortality rate of 29.9%…”
Section: Introductionmentioning
confidence: 99%
“…Although they report differing mortality rates they all exhibit high rates of suicide, 32%, 22.7% and 50% of the reported deaths, respectively. In addition, Fazel et al 11 noted the death of 14.2% of their cohort and Clarke et al 12 22.8% of deaths from accidental/unnatural causes.…”
Section: All-cause Mortality In Forensic Settingsmentioning
confidence: 98%
“…[1][2][3] The number of years of life lost in relation to all-cause mortality varies from 7 to 24 depending on the nature of the condition. 2 Substance use disorder (SUD) conveys the highest potential number of years lost (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24); however, this is closely followed by the ranges for personality disorders (13-22 years), schizophrenia (10-20 years) and bipolar disorder (9-20 years) demonstrating a psychophysiological influence (which we define as a physiological response mediated by biochemical pathways to psychological distress) upon morbidity/mortality beyond the physical impact of illicit substances.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the staffing levels in forensic wards are high compared to general psychiatric in-patient care. These circumstances result in high care costs, and forensic psychiatry often represents a large part of the overall psychiatry budget, while the population is rather small in terms of the number of patients (3).…”
Section: Introduction Rationalementioning
confidence: 99%